Avaliação de habilidades sociais de adolescentes em conflito com a lei em interações com familiares e amigos : uma análise de metacontingências - Fogaça, Fabiane Ferraz Silveira (Universidade Federal de São Carlos, 2015)
The study of juvenile offender’s interactions with mother, brother, and friend indicates which categories of social skills (assertiveness, self-control, conversation, and empathy) are established by shaping and modeling processes. Furthermore, it produces more evidences to the relationship between prosocial and antisocial behavior. This study aimed to describe a set of interlocking behavioral contingencies (IBCs) comprised by categories of social skills, which in turn contribute to legal measures outcomes. This study is made up by three independent chapters. The chapter 1. “Social skills of young offenders and at risk adolescents” discussed the social skills repertories as one of multiple factors of evaluation and intervention with adolescents. In summary, the outcomes indicated improvement on social skills categories, specially presented in home settings, the decrease of offending persistence, and lower evidences of the impact of social skills improvements on other adults and peers relationships. The chapter 2, named “Contributions of conceptual, descriptive and experimental metacontingencies studies to family interactions”, explored the metacontingency unit of analysis. Specifically, it discussed the interpersonal relationship patterns as behavioral products transmitted along family members. The last chapter, named “Identifying social skills repertoires in juvenile offenders´ interactions with relatives and friends: a metacontingencies analysis” aimed to describe IBCs that contribute to legal measures results. The participants were three families composed by a mother, a juvenile offender, and a brother without a history of delinquency. Self-reports instruments and interviews were used. The data analysis procedures were as follows: the development of IBCs coding system, establishing relationship between categories of IBCs and categories of social skills, and establishing relationship between categories of IBCs and categories of aggregate products. The results suggested that the participants, who achieved better scores on socials skills categories, also got engaged in conversation, support, negotiation, cooperation, and rules establishment interactions. Also they achieved some of the goals of legal measures (aggregate products).
Social skills evaluation in juvenile offender interactions with relatives and friends : A metacontingency analysis
Keywords: Família; Adolescente em conflito com a lei; Habilidades sociais; Metacontingências; Juvenile offender; Family; Social skilss; Metacontingencies; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::RELACOES INTERPESSOAIS